2021
DOI: 10.21037/atm-20-3399
|View full text |Cite
|
Sign up to set email alerts
|

MiR-4729 regulates TIE1 mRNA m6A modification and angiogenesis in hemorrhoids by targeting METTL14

Abstract: Background: Hemorrhoids are a frequently-occurring disease of the anorectal system that is often accompanied by vascular hyperplasia and edema. A METTL14-mediated RNA N-6 methyladenosine (m6A) modification can improve mRNA stability and increase its transcriptional and translational activities, closely related to the occurrence of many diseases.Methods: Western blot, qPCR, and immunofluorescence staining were used to detect the levels of gene and protein expression. Haematoxylin and eosin staining was used for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…The expression of VEGFA and its splice variants, VEGFA-164 and VEGFA-188, is inhibited in METTL3-deficient bone marrow stromal cells [205]. In addition, METTL14, one of the m6A methylase components, plays an active role in regulating cardiovascular endothelial cell proliferation, invasion [206] and angiogenesis in haemorrhoids [207].…”
Section: M6a Modification and Ocular Angiogenetic Diseasesmentioning
confidence: 99%
“…The expression of VEGFA and its splice variants, VEGFA-164 and VEGFA-188, is inhibited in METTL3-deficient bone marrow stromal cells [205]. In addition, METTL14, one of the m6A methylase components, plays an active role in regulating cardiovascular endothelial cell proliferation, invasion [206] and angiogenesis in haemorrhoids [207].…”
Section: M6a Modification and Ocular Angiogenetic Diseasesmentioning
confidence: 99%
“…Another in vivo experiment showed that silencing the eraser FTO in ECs can induce hyper-methylation on critical proangiogenic genes, such as FAK, which were recognized by the m 6 A reader YTHDF2 to induce RNA decay, thus regulating ocular angiogenesis (Shan et al, 2020). In comparison, angiogenesis is regulated by miR-4729, which inhibits METTL14 to decrease the m 6 A methylation of TIE1 and further inhibit TIE1/VEGFA signaling pathways in vascular ECs (Liu et al, 2021). In addition, FTO plays a vital role in cardiac contraction function, remodeling, regenerative repair, and cardiac homeostasis.…”
Section: Role Of Rna Modification In Angiogenesis M 6 a In Physiologi...mentioning
confidence: 99%
“… 50 In vascular endothelial cells, the expression level of METTL14, modulated by miR‐4729, is reduced, resulting in declination in m6A modification level of TIE1 mRNA 3′UTR specific site, TIE1 mRNA stability reduction, and angiogenesis inhibition. 51 In renal cell carcinoma, METTL14 is regulated by the competitive binding effect of circRNAs and miRNAs, and affects the expression of downstream molecule PTEN and changes in related AKT/PKB signals. 52 In skin tumors, METTL14 acts as the target of NBR1‐dependent selective autophagy, and its expression level is down‐regulated.…”
Section: Modulation Of Mettl14 Expressionmentioning
confidence: 99%